Aerodynamics of nominally circular cylinders: A review of experimental results for Civil Engineering applications. (15th April 2017) - Demartino, C.; Ricciardelli, F.
Highlights: We reviewed the state of art of the aerodynamics of nominally circular cylinders. We consider only experimental results. Deviations are classified into cylinder and flow irregularities. Cylinder irregularities are classified in surface, section and spanwise irregularities. Abstract: Fluid-dynamic loads have a great influence on the design of many Civil Engineering structures. In particular, circular sections are widely used in constructions, yet when it comes to aero- or hydro-dynamics simple geometry brings a complex behavior, as the features of flow separation strongly depend on Reynolds number. This has triggered a remarkable research effort towards the understanding of the aerodynamic behavior of circular cylinders. Indeed, circular cylinders used in Engineering applications are seldom perfect ones. In many cases, it has been observed that imperfections affect aerodynamics to a large extent. For this reason, a considerable effort has also been devoted to the understanding of how aerodynamics is modified by imperfections. This paper contains a review of existing literature on experimental results of interest for Civil Engineering applications on the aerodynamics of cylinders, whose geometry deviates from that of a perfect circular cylinder. Such deviations are classified into cylinder and flow irregularities, and the former are further subdivided into surface, section and spanwise irregularities. The need for further research is pointed out at the end of the paper.